Craniometric asymmetry assessment in class I and class II skeletal relationship patients using helical computed tomography sample aged between 18-35 years - Uday A Taha; Lamia H Al-Nakib (College of Dentistry/ University of Baghdad, 2013)
Background: Asymmetry assessment is an important component of orthodontic diagnosis and treatment planning. Several studies attempted to find the relationship between craniometric asymmetry and skeletal jaws relationship and many authors found some extent of asymmetry in individuals with normal jaws relationship. The use of Computed tomography (CT) allows for the assessment of asymmetry on a dimensionally accurate volumetric image, aim of the study is to determine if there are differences in craniometric asymmetry between patient with skeletal class I and patients with skeletal class II relationship using Helical CT scan. Materials and Methods: Ninety individuals with clinically symmetrical faces were imaged with Helical CT scan, and aging 18-35 years, divided into two groups, class ? group consisted of 31 individuals and class ?? group consisted of 59individuals. Anatomical landmarks were defined and reference planes were established to determine the variance of the landmarks using a coordinate plane system. Sagittal radiographs were used to determine the amount of the ANB angle. Asymmetry was analyzed by calculating the linear measurements and asymmetry indices of the anatomical landmarks by using coronal and axial radiographs in both classes. Results: Clinically symmetrical faces demonstrated a computed tomographic significant asymmetry with the vertical dimensions being significantly larger than the bilateral dimensions and the amount of asymmetry was more at the level of the mandible and less at the maxillary area. Conclusions: The craniometric structures in terms of size and shape were larger in males than in females. The amount of asymmetry was independent on gender and skeletal jaws relationship and age.